Identification and Characterization of 16SrIX and 16SrXI groups of phytoplasmas associated with leaf yellows and declining disease of garlic and onion in India - VIPOOL THORAT, AMIT YADAV and G.P. RAO*, SONIA GOEL, MADHUPRIYA (Indian Phytopathology, 2017)
Leaf yellows and declining symptoms were observed on garlic and onion plants at Pune and Nasik region of Maharashtra, and Gorakhpur region of Uttar Pradesh in March-April 2016. The disease incidence varied from 12% to 30% in different surveyed regions. After nucleic acid extraction and nested PCR analysis using phytoplasma specific primer pairs (P1/P7 followed by 3F/3R) of 16S ribosomal gene an expected DNA fragments of 1.3 kb were amplified in two onion symptomatic samples (from Gorakhpur and Narayangaon) and one garlic symptomatic sample (from Pune). Pair wise sequence comparison of 16S rDNA sequence analysis of the onion leaf yellows phytoplasma (GKP strain) showed 100 percent sequence identity with strain of sugarcane grassy shoot phytoplasma (KP746932) and 99 percent sequence identity with strains of Jasminum sambac little leaf phytoplasma (KF728950) and Ca. P. oryzae (AB052873) belonging to rice yellow dwarf (16SrXI) group. However, another strain of onion leaf yellows phytoplasma (Narayangaon strain) and garlic leaf yellows and declining phytoplasma (Pune strain) showed 99 percent sequence identity with phytoplasma strains of grapevine yellows (KX011516), eggplant big bud (JX464672) and sesame phyllody (JX464672) belonging to Ca. P. phoenecium (16SrIX) group. Phylogenetic analysis of 16Sr DNA sequences of phytoplasma strains from onion and garlic in the present study confirmed their close relationships with phytoplasma strains of 16SrXI and 16SrIX groups. This is the first report of association of 16SrXI and -IX groups of phytoplasma causing leaf yellows and declining disease of onion and garlic in India.